DETERMINATION OF INSTALLATION PARAMETERS FOR FORMATION OF BRICK PREPARATIONS THAT PROVIDE MINIMUM ERROR OF MOVING - PEREPELITSYA, Vyacheslav; KOZLOV, Leonid (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents examples of modern mechanisms that in the process of their work require the simultaneous execution of two or more movements. Methods of synchronization of several hydraulic drives depending on the operating conditions of such mechanisms are considered. There are methods for using a throttle flow divider, a flow divider with an adjustable ratio, two independent circuits with their combination using a fuzzy logic controller, and others. The relevance of the optimal selection of design parameters that directly affect the error of motion synchronization is substantiated. A variant of improving the cutting machine for forming brick blanks by replacing the mechanical structure with a hydraulic drive is proposed, its main advantages are determined. The hydraulic scheme of the installation for forming a brick blank is presented, and the principle of operation of this device is described. A mathematical model of the dynamics of the carriage motion of an installation for brick formation has been developed, which is represented by a system of nonlinear differential equations. Rosenbrock's method was used to solve the developed system. The block diagram of solving the equation of operation of the hydraulic cylinder of the installation for the formation of brick blanks is presented and a simulation study of the dynamics of the carriage of the installation in the environment of MATLAB Simulink. As a result of the study, the dependences of the speed of movement and movement of the carriage of the installation for the formation of brick blanks were obtained. The dependences of the influence of the most important parameters on the value of the error of the carriage movement of the installation for the formation of brick blanks are determined. These parameters are: the area of the working window of the throttle, the area of the auxiliary hydraulic cylinder and the stiffness of the spring. Numerical values of parameters at which the error of movement of the carriage of the installation for formation of a brick concerning a clay bar will be minimum are recommended.
Keywords: installation for forming brick blanks; mathematical model; throttle; spring; displacement error; motion synchronization